Tiger or turtle? exploring alternative futures for Egypt to 2020 - Lofgren, Hans; Robinson, Sherman; Nygaard, David F. (The American University in Cairo Press, 1998)
A dynamic computable general equilibrium (CGE) model is used to explore alternative scenarios for 1990-2020 in areas critical for Egypt's economy -- productivity growth, investment, foreign trade, and water. The model is formulated as a mixed-complementarity problem, has a detailed treatment of agriculture, assumes competitive markets and determines efficient water allocation. A "Turtle" scenario extrapolates Egypt's recent poor productivity and low investment, while a "Tiger" scenario assumes East Asian performance. For the Turtle scenario, incomes are stagnant and a crisis emerges in the labor market. With rapid growth in export demand, investment and productivity, the "Tiger" scenario generates almost tripled per-capita incomes and full employment. Sensitivity analysis for the Tiger scenario suggests that growth in export demand is important, while tariff removal with no other policy changes has little effect. Increasing water scarcity hurts agriculture and labor absorption, but has little effect on overall growth.